2015
DOI: 10.1186/s12864-015-1440-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profile of sweet orange in response to chitosan and salicylic acid

Abstract: BackgroundResistance inducers have been used in annual crops as an alternative for disease control. Wood perennial fruit trees, such as those of the citrus species, are candidates for treatment with resistance inducers, such as salicylic acid (SA) and chitosan (CHI). However, the involved mechanisms in resistance induced by elicitors in citrus are currently few known.ResultsIn the present manuscript, we report information regarding the transcriptional changes observed in sweet orange in response to exogenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 79 publications
5
40
0
1
Order By: Relevance
“…S1), paralleling the higher impact of this stress combination on plant physiology, compared to individual stress components. In the present work, SA accumulation pattern was similar, finding the highest hormone content as well as the up‐regulation of ICS (SA‐biosynthetic gene, Dempsey et al ) and PR2 (a SA‐inducible gene, Coqueiro et al ) in plants subjected to combined moderate drought and heat (Fig. ).…”
Section: Discussionsupporting
confidence: 80%
“…S1), paralleling the higher impact of this stress combination on plant physiology, compared to individual stress components. In the present work, SA accumulation pattern was similar, finding the highest hormone content as well as the up‐regulation of ICS (SA‐biosynthetic gene, Dempsey et al ) and PR2 (a SA‐inducible gene, Coqueiro et al ) in plants subjected to combined moderate drought and heat (Fig. ).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to chitin, chitosan appears to elicit activity from plant cells via charge–charge interactions with negatively charged phospholipids instead of via a receptor-specific interaction (Kauss et al 1989). The differential expression of key elements under SA and chitosan treatment were investigated by Coqueiro et al (2015) in orange by RNA-seq technology. More genes were induced by SA treatment than by chitosan treatment.…”
Section: Biocontrol and Other Agricultural Applicationsmentioning
confidence: 99%
“…More genes were induced by SA treatment than by chitosan treatment. Under chitosan treatment, there were 640 differentially expressed genes, many of them involved in secondary metabolism and the treatment also altered some hormone metabolism pathways (Coqueiro et al 2015). It was found that chitosan amendment increased plant phenylalanine ammonia lyase activity, which is the crucial enzyme of phenylpropanoid metabolism, and the subsequent increase in phenolic content, polyphenol oxidase, peroxidase, and chitinase is a general response associated with disease resistance (Anand et al 2009; Mejía-Teniente et al 2013).…”
Section: Biocontrol and Other Agricultural Applicationsmentioning
confidence: 99%
“…Expansins (EXPs) are cell wall structural proteins which regulate wall expansion during cell growth [1] and stress responses [2] by weakening the hydrogen bond between cell wall polysaccharides. Emerging studies showed that phytohormones interact with the EXPs to coordinate many physiological and cellular processes of plant growth in response to developmental and environmental stimuli [3][4][5]. Phytohormones, including cytokinin, jasmonate, and gibberellin, induce the expression of EXP superfamily [6].…”
Section: Introductionmentioning
confidence: 99%